E-PEER MENTORING EFFECTIVENESS: A CASE STUDY FOR MATHEMATICS COURSE AT UITM CAWANGAN KELANTAN - Masnira Ramli; Mardhiyah Ismail; Suziana Aida Othman; Siti Farah Haryatie Mohd Kanafiah; Mohd Faiez Suhaimin (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The universities closures due to the COVID-19 pandemic led to the sudden shift from classrooms to virtual learning and most of the students are unable to be physically around in the campus. This situation has caused some significant problems in teaching and learning not only to the lecturers, but it also affects the students especially in learning mathematics. Hence, the E-Peer Mentoring Program is conducted via online platform as a proactive measure to facilitate the students in learning mathematics. The objectives of this research paper are: first, to determine the significant mean difference between E-Peer Mentoring Program effectiveness and gender, second, to determine the relationship between leadership skills, mentor-mentee relationships, and communication methods between mentor-mentees towards E-peer Mentoring Program effectiveness, and third, to determine the most important factors that contribute to the E-Peer Mentoring Program effectiveness. The questionnaires were distributed to 80 students involved in this program. The findings showed that the E-Peer Mentoring Program effectiveness among student’s gender is equal whereas the gender stereotype on how they viewed this program do not apply for these students. The findings also revealed that there were significant positive relationships between leadership skill, mentor-mentee relationships and communication methods between mentor-mentees towards the program effectiveness. From these three factors, only the mentor-mentee relationships and communication methods between mentor-mentees were perceived as the most important factors that contributed to the program effectiveness. This suggests that the good relationship between mentor and mentees and effective communication between them had proven to have positive impacts to the program effectiveness.